2012
DOI: 10.1073/pnas.1019605109
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme functional evolution through improved catalysis of ancestrally nonpreferred substrates

Abstract: In this study, we investigated the role for ancestral functional variation that may be selected upon to generate protein functional shifts using ancestral protein resurrection, statistical tests for positive selection, forward and reverse evolutionary genetics, and enzyme functional assays. Data are presented for three instances of protein functional change in the salicylic acid/benzoic acid/theobromine (SABATH) lineage of plant secondary metabolite-producing enzymes. In each case, we demonstrate that ancestra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 54 publications
2
98
0
Order By: Relevance
“…The existence of exapted ancestral enzymes such as CisAncXMT2 resolves one of the fundamental problems of the cumulative hypothesis because multiple steps of a pathway could evolve simultaneously, thereby avoiding the need to assume the existence of selectively advantageous intermediates. These results also point to a crucial role for ancestral promiscuous activities postulated as part of the patchwork hypothesis and protein engineering studies (31) and reported previously for other SABATH enzymes (46).…”
Section: Exaptation Facilitates Multistep Pathway Evolution In a Cumusupporting
confidence: 82%
See 2 more Smart Citations
“…The existence of exapted ancestral enzymes such as CisAncXMT2 resolves one of the fundamental problems of the cumulative hypothesis because multiple steps of a pathway could evolve simultaneously, thereby avoiding the need to assume the existence of selectively advantageous intermediates. These results also point to a crucial role for ancestral promiscuous activities postulated as part of the patchwork hypothesis and protein engineering studies (31) and reported previously for other SABATH enzymes (46).…”
Section: Exaptation Facilitates Multistep Pathway Evolution In a Cumusupporting
confidence: 82%
“…Ancestral O-methylation of the carboxyl moiety of benzoic and salicylic acid might have promoted the evolution of N-methylation of xanthine alkaloids because of common attributes of the active sites that would need to accommodate the largely planar rings of both classes of substrates. Indeed, a paralogous SABATH methyltransferase specialized for methylation of the carboxyl group of nicotinic acid (which is also an N-heterocyclic substrate) also recently arose from ancestral enzymes that exhibited activities with benzoic and salicylic acid (46). Although these data indicate that ancestral activity with benzoic and salicylic acid in the XMT lineage allowed for subsequent co-option of the descendant enzymes to form caffeine, how recruitment of the enzymes into a functional pathway occurred remains unknown.…”
Section: Historical Maintenance Of Ancestral Xmt Enzymes Allowed Formentioning
confidence: 99%
See 1 more Smart Citation
“…Physical modeling of amino acid chains suggests that EAC preferentially takes place under moderate selective pressure and therefore likely in genes that are not essential for survival, but that can substantially improve fitness if optimized (Sikosek et al, 2012). So far, duplicate gene evolution by EAC has been mainly a theoretical model and only few cases indicating EAC have been documented (DesMarais and Rausher, 2008;Deng et al, 2010;Huang et al, 2012). One reason for the scarcity of examples is related to the difficulty 13 to ascertain whether the criteria for EAC are fulfilled, in particular whether functions were improved compared to the ancestral gene and whether this improvement was really constrained before duplication (Barkman and Zhang, 2009).…”
Section: Subfunctionalization By Escape From Adaptive Conflict (Eac)mentioning
confidence: 99%
“…Central to this "patchwork" model of pathway evolution is the notion that many enzymes have limited substrate specificities and can catalyze, albeit at low rates, reactions other than those for which they have evolved (also referred to as enzyme promiscuity) (4). These so-called underground (5) or side activities are prevalent (6)(7)(8) and were shown to serve as starting points for the evolution of novel functions both in directed evolution experiments (9) and in the diversification of gene families in the wild (7). However, how the underground catalytic repertoire encoded in the genome can generate novelties within the context of the existing metabolic network remains unknown.…”
mentioning
confidence: 99%